Mesoproterozoic suturing of Archean crustal blocks in western peninsular India: Implications for India-Madagascar correlations - Ishwar-Kumar, C.; Santosh, M.; Wilde, Simon; Tsunogae, T.; Itaya, T.; Windley, B.; Sajeev, K. (Elsevier BV, 2015)
The Kumta and Mercara suture zones welding together Archean crustal blocks in western peninsular India offer critical insights into Precambrian continental juxtapositions and the crustal evolution of eastern Gondwana. Here we present the results from an integrated study of the structure, geology, petrology, mineral chemistry, metamorphic P-T conditions, zircon U-Pb ages and Lu-Hf isotopes of metasedimentary rocks from the two sutures. The dominant rocks in the Kumta suture are greenschist- to amphibolite-facies quartz-phengite schist, garnet-biotite schist, chlorite schist, fuchsite schist and marble. The textural relations, mineral chemistry and thermodynamic modelling of garnet-biotite schist from the Kumta suture indicate peak metamorphic P-T conditions of ca. 11kbar at 790°C, with detrital SHRIMP U-Pb zircon ages ranging from 3420 to 2547Ma, eHf (t) values from -9.2 to 5.6, and TDM c model ages from 3747 to 2792Ma. The K-Ar age of phengite from quartz-phengite schist is ca. 1326Ma and that of biotite from garnet-biotite schist is ca. 1385Ma, which are interpreted to broadly constrain the timing of metamorphism related to the suturing event. The Mercara suture contains amphibolite- to granulite-facies mylonitic quartzo-feldspathic gneiss, garnet-kyanite-sillimanite gneiss, garnet-biotite-kyanite-gedrite-cordierite gneiss, garnet-biotite-hornblende gneiss, calc-silicate granulite and metagabbro. The textural relations, mineral chemistry and thermodynamic modelling of garnet-biotite-kyanite-gedrite-cordierite gneiss from the Mercara suture indicate peak metamorphic P-T conditions of ca. 13kbar at 825°C, followed by isothermal decompression and cooling. For pelitic gneisses from the Mercara suture, LA-ICP-MS U-Pb zircon ages vary from 3249 to 3045Ma, eHf (t) values range from -18.9 to 4.2, and TDM c model ages vary from 4094 to 3314Ma. The lower intercept age of detrital zircons in the pelitic gneisses from the Mercara suture ranges from 1464 to 1106Ma, indicating the approximate timing of a major lead-loss event, possibly corresponding to metamorphism, and is broadly coeval with events in the Kumta suture. Synthesis of the above results indicates that the Kumta and Mercara suture zones incorporated sediments from Palaeoarchean to Mesoproterozoic sources and underwent high-pressure metamorphism in the late Mesoproterozoic. The protolith sediments were derived from regions containing juvenile Palaeoarchean crust, together with detritus from the recycling of older continental crust. Integration of the above results with published data suggests that the Mesoproterozoic (1460-1100Ma) Kumta and Mercara suture zones separate the Archean (3400-2500Ma) Karwar-Coorg block and Dharwar Cratons in western peninsular India. Based on regional structural and other geological data we interpret the Kumta and Mercara suture zones as extensions of the Betsimisaraka suture of eastern Madagascar into western India.